2013
DOI: 10.1186/1471-2393-13-9
|View full text |Cite
|
Sign up to set email alerts
|

Need for insulin to control gestational diabetes is reflected in the ambulatory arterial stiffness index

Abstract: BackgroundThe aim was to evaluate the metabolic profile in conjunction with vascular function using the ambulatory arterial stiffness index (AASI) in women with uncomplicated pregnancies and in women with gestational diabetes mellitus (GDM).MethodsPlasma glucose, lipids, HOMA –IR (homeostasis model assessment of insulin resistance) and AASI, as obtained from 24-hour ambulatory blood pressure monitoring in third trimester pregnancy and at three months postpartum, were measured in three groups of women: controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…However, the use of insulin in women with GDM has disadvantages, including the lack of a clear definition of the dose, the need for multiple daily injections and the risk of hypoglycaemia and maternal weight gain (Norman et al 2004). In addition, some women administered insulin for GDM exhibit metabolic alterations at 3 months postpartum, a phenomenon associated with maternal arterial stiffness (Kärkkäinen et al 2013). Other studies also indicate that insulin therapy during GDM is associated with an increased risk for developing type 1 diabetes mellitus (Löbner et al 2006).…”
Section: Insulin Therapy In Gdmmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of insulin in women with GDM has disadvantages, including the lack of a clear definition of the dose, the need for multiple daily injections and the risk of hypoglycaemia and maternal weight gain (Norman et al 2004). In addition, some women administered insulin for GDM exhibit metabolic alterations at 3 months postpartum, a phenomenon associated with maternal arterial stiffness (Kärkkäinen et al 2013). Other studies also indicate that insulin therapy during GDM is associated with an increased risk for developing type 1 diabetes mellitus (Löbner et al 2006).…”
Section: Insulin Therapy In Gdmmentioning
confidence: 99%
“…In addition, some women administered insulin for GDM exhibit metabolic alterations at 3 months postpartum, a phenomenon associated with maternal arterial stiffness (Kärkkäinen et al . ). Other studies also indicate that insulin therapy during GDM is associated with an increased risk for developing type 1 diabetes mellitus (Löbner et al .…”
Section: Introductionmentioning
confidence: 97%
“…However, no statistically significant difference was found in arterial stiffness between these groups. Karkkainen et al (39) showed that there was a similar increase in arterial stiffness in both the groups, but it was reversible in the non-insulin requiring GDM group and normalized in the postpartum period, whereas it was not in the insulin-requiring GDM group. However, the number of GDM patients, requiring insulin, was very low (n=6).…”
Section: Discussionmentioning
confidence: 94%
“…The ambulatory arterial stiffness index (AASI) has been shown to correlate with other techniques of measuring arterial stiffness such as pulse wave velocity and augmentation index, and it has been claimed to be capable of detecting arterial dysfunction at a younger age than is possible with pulse pressure . (Karkkainen et al, 2011(Karkkainen et al, , 2013. (Leoncini et al, 2006;Mule et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously examined AASI in uncomplicated singleton and twin pregnancies and in pregnancies complicated by gestational diabetes mellitus. (Karkkainen et al, 2011(Karkkainen et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%